Researcher–teacher collaboration: A contextual framework for creating scalable, social-justice-oriented literacy materials - Rojas-Alfaro, Roberto (2026)
This design-based qualitative study examined researcher–teacher collaboration in creating digital storybooks for rural sixth-grade classrooms in Costa Rica. Specifically, it sought to explore how a pedagogical design framework can inform creating digital storybooks that supports bilingual (Spanish/English) literacy through digital storytelling. Three experienced rural English teachers joined four online workshops between March and May 2024 to co-establish a pedagogical framework integrating culturally responsive teaching, Fraser’s social-justice dilemmas (redistribution, recognition, representation), and national English curriculum objectives. The team then used ChatGPT within FUNREAD – a web-based digital storytelling platform supporting Spanish/English literacy instruction – to generate beginning-level (CEFR-A1) storybooks. Field notes, transcripts, and participant feedback were thematically analyzed to trace design decisions across three phases: selecting social-justice dilemmas, mapping curricular themes, and crafting artificial intelligence (AI) prompts. The prototype storybook, “Susana’s Dream” – centered on Costa Rican NASA scientist Sandra Cauffman – illustrates how context-sensitive narratives can advance vocabulary, grammar, and critical awareness simultaneously. Findings demonstrate that structured co-design empowers teachers to embed equity, identity, and community relevance in literacy materials, while generative AI scales production without displacing pedagogical expertise.